Idiopathic catastrophic thrombosis with happy ending - Heid, Julia; Greinacher, Andreas; Katus, Hugo; Müller, Oliver J. (BMJ case reports, 2017)
A 59-year-old male patient suffered three life-threatening instent thromboses after an initial resuscitation due to an ST-segment elevation myocardial infarction of the anterior cardiac wall. With a high-risk profile for heparin-induced thrombocytopenia (HIT), he was placed on argatroban after the second reinfarction. Under this apparently appropriate treatment, a third reinfarction occurred, and the patient had to undergo high-risk cardiac bypass surgery. Later on, a deep vein thrombosis and an intracardiac thrombus formed. Despite a positive screening test for HIT and a single positive result in the heparin-induced platelet aggregation test, we are not convinced that HIT was the only underlying cause for this ‘catastrophic thrombotic syndrome’. We speculate that a massive generation of thrombin, reflected in consistently high D dimers and the need of copious amounts of a direct thrombin inhibitor, triggered the set of events. With this case report, we want to raise awareness for cardiac complications in patients with complex clotting disorders and share our experience in the diagnostic and therapeutic management of such an unusual scenario.